2005
DOI: 10.1136/jmg.2005.031476
|View full text |Cite
|
Sign up to set email alerts
|

A common variant of CDKN2A (p16) predisposes to breast cancer

Abstract: Background: A common missense variant of the CDKN2A gene (A148T) predisposes to malignant melanoma in Poland. An association between malignant melanoma and breast cancer has been reported in several families with CDKN2A mutations, Objective: To determine whether this variant also predisposes to breast cancer. Methods: Genotyping was undertaken in 4209 cases of breast cancer, unselected for family history, from 18 hospitals throughout Poland and in 3000 controls. Results: The odds ratio (OR) associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 23 publications
4
68
1
Order By: Relevance
“…The known SNP, A148T found in three tumors (5%) is reported in 6% of the global and 3% of the European population (http://www.ncbi.nlm.nih.gov/ SNP/snp_ref.cgi?rsZ3731249). It has also been reported as a predisposing alteration in connection to malignant melanoma and breast and lung cancer (Debniak et al 2005, Puig et al 2005. None of the detected sequence alterations occurred in conjunction with malignant disease.…”
Section: Discussionmentioning
confidence: 96%
“…The known SNP, A148T found in three tumors (5%) is reported in 6% of the global and 3% of the European population (http://www.ncbi.nlm.nih.gov/ SNP/snp_ref.cgi?rsZ3731249). It has also been reported as a predisposing alteration in connection to malignant melanoma and breast and lung cancer (Debniak et al 2005, Puig et al 2005. None of the detected sequence alterations occurred in conjunction with malignant disease.…”
Section: Discussionmentioning
confidence: 96%
“…2 Some studies have reported associations of hypermethylation of CDKN2A 6 or the A148T polymorphism in association with breast cancer risk as well. 7 Brain, head/neck and nonmelanoma skin cancer have also been reported to be more common among mutation carriers. [8][9][10] The CDKN2A gene encodes two different proteins, read from alternate reading frames of a common second exon.…”
Section: Introductionmentioning
confidence: 99%
“…www.intechopen.com however, according to Debniak and co-workers (Debniak et al, 2005a) we can not exclude the possibility that it subtly affects p16 INK4a function or reduces its level of expression.…”
Section: Cdkn2a Germline Mutations In Multiple Primary Malignanciesmentioning
confidence: 87%
“…Next they studied whether the same variant exhibits breast-cancer-predisposing nature too and found that the odds ratio associated with the CDKN2A allele for women diagnosed with breast cancer before the age of 50 was 1.5 and after the age of 50 it was 1.3. The effect was the strongest for women diagnosed at or before the age of 30 (Debniak et al, 2005a), suggesting a role of the A148T polymorphism in breast cancer predisposition. As a next step, the workgroup performed a population-based study where they compared the genotypes and the allele frequency of the A148T polymorphism in the group of 3,583 unselected cancer cases and 3,000 random controls.…”
Section: Cdkn2a Germline Mutations In Multiple Primary Malignanciesmentioning
confidence: 94%